2020
DOI: 10.1177/2333393620950241
|View full text |Cite
|
Sign up to set email alerts
|

Patient Centeredness from a Perspective of History of the Present: A Genealogical Analysis

Abstract: The overall aim of this study, performed in Sweden, was to problematize the contemporary national and transnational discourse on patient centeredness, which during recent decades has become a given, having become established as a dogma in conversations, writing, and thinking about patients and health care. We did that by showing that ideas such as patient centeredness can be seen differently from the way they are depicted in contemporary discourses about health care. In the presented analysis, we drew on Fouca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Our results reaffirm the importance of ward rounds for patients and indicate that providing them the opportunity to attend routine ward rounds through real-time notifications may lead to improved inpatient satisfaction. Patient-centeredness is an essential component of high-quality healthcare, contributing to improved experience and clinical outcomes [15]. It is defined by the Institute of Medicine as the establishment of a partnership between the patient and healthcare providers to ensure that the wishes, needs, and preferences of the former are respected in the shared decision-making process [16].…”
Section: Discussionmentioning
confidence: 99%
“…Our results reaffirm the importance of ward rounds for patients and indicate that providing them the opportunity to attend routine ward rounds through real-time notifications may lead to improved inpatient satisfaction. Patient-centeredness is an essential component of high-quality healthcare, contributing to improved experience and clinical outcomes [15]. It is defined by the Institute of Medicine as the establishment of a partnership between the patient and healthcare providers to ensure that the wishes, needs, and preferences of the former are respected in the shared decision-making process [16].…”
Section: Discussionmentioning
confidence: 99%
“…In the field of PFCC research, we have observed that this results in more kinds of ‘centring’ theories and further theoretical ambiguity. For example, Siouta and Olsson (2020) conducted a policy analysis of patient centredness in Sweden and found ‘that contemporary narratives about centeredness are neither more, nor less, care seeker‐centred than the narratives of yesteryear’ (p. 9). These authors, while problematising current ‘centring’ policies, suggested a different kind of person‐centred care, which does not particularly inspire more interesting or innovative research in this field.…”
Section: Discussion: Decentring Care Practicesmentioning
confidence: 99%